A correlation coefficient‐based algorithm for fault detection and classification in a power transmission line. Issue 10 (23rd May 2018) - Musa, Mohammed H. H.; He, Zhengyou; Fu, Ling; Deng, Yujia
Abstract : This paper presents a new algorithm for fault detection and classification in a power transmission line. The fundamental idea of the proposed algorithm is the calculation of the correlation coefficient (CC) between the current signal of each phase of the three‐phase system and its reference value. The following rule makes the decision of detecting and classifying the fault condition: when the system is running under healthy condition, the correlation between the current signal of each phase and its reference value is very strong; when the system is in faulty condition, the correlation between the current signal of each phase and its reference value is low compared to that in the healthy condition. The new algorithm is applied to a power transmission line model established in PSCAD/EMTDC. Different fault circumstances such as different inception times, different fault resistances, and different locations have been verified. Additionally, far‐end faults with high resistance, faults occurring near a terminal, faults considering variable loading angle, and faults in the presence of noise are easily detected by the proposed method. For each possible scenario of fault, the proposed algorithm requires only the three‐phase current measurement of the local measurement unit. The results show satisfactory performance in most cases. © 2018 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.